Assessment Of The Demographic Profile And Current Status Of Gender Mainstreaming In Agricultural Extension Services In Uttar Pradesh. - Aman Verma; Veenita Kumari; Amrit Warshini (Journal of Agricultural Extension Management, 2026)
This study examines the implementation and effectiveness of gender mainstreaming strategies in agricultural extension services across four districts of Uttar Pradesh, India. Using a descriptive research design, the study surveyed 60 extension personnel across Hamirpur, Unnao, Amethi, and Agra districts. The research findings reveals significant gender disparities within extension services, with women comprising only 21.67 percent of the extension personnel and 93.33 percent of the organisations reporting merely 0-20.00 percent female field officers. Despite these imbalances, 70.00 percent of the extension personnel actively implement gender-inclusive strategies, including minimum participation quotas, collaboration with women’s groups, and schedule adapted to accommodate women’s needs. The study finds that 81.67 percent of the personnel consistently collected sex-disaggregated data, though implementation challenges persist, including insufficient fund, cultural constraints, and logistic barriers. Critical gender mainstreaming activities include gender sensitivity training, partnerships with Anganwadi workers, establishment of women’s Self-Help Groups, mobile-based advisory services, and technical workshops. The research study highlights the need for increased recruitment of female extension officers, enhanced monitoring systems, and dedicated funding for gender-focused programs to address persistent gaps in agricultural extension services. These findings contribute to understanding the current state of gender mainstreaming in agricultural extension and provide actionable recommendations for improving gender equality in agricultural development.